2018
DOI: 10.1158/0008-5472.can-17-1339
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase Inhibition by AT13148 Blocks Pancreatic Ductal Adenocarcinoma Invasion and Tumor Growth

Abstract: The high mortality of pancreatic cancer demands that new therapeutic avenues be developed. The orally available small molecule inhibitor AT13148 potently inhibits ROCK1 and ROCK2 kinases that regulate the actomyosin cytoskeleton.We previously reported that ROCK kinase expression increases with human and mouse pancreatic cancer progression and that conditional ROCK activation accelerates mortality in a genetically modified LSL-KrasG12D; LSL-p53R172H; Pdx1-Cre; (KPC) mouse pancreatic cancer model. In this study,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 47 publications
3
63
0
Order By: Relevance
“…We found that inhibition of ROCK triggers the formation of leaders and the transition from non‐invasive to protrusive cohorts that undergo collective invasion. This is in contradiction with the pro‐invasive role of ROCK identified in CIMP CRCs explants (Zajac et al , ), mice xenografted with cell lines (Itoh et al , ; Croft et al , ; Sadok et al , ) or transgenic models of pancreatic cancer (Rath et al , ). However, our results are in agreement with the recent large‐scale in vivo RNAi screen revealing that loss of Myosin‐II triggers the formation of invasive skin cancers (Schramek et al , ) and that expression of active ROCK2 increases proliferation, but not invasion in similar models (Samuel et al , ).…”
Section: Discussionmentioning
confidence: 88%
“…We found that inhibition of ROCK triggers the formation of leaders and the transition from non‐invasive to protrusive cohorts that undergo collective invasion. This is in contradiction with the pro‐invasive role of ROCK identified in CIMP CRCs explants (Zajac et al , ), mice xenografted with cell lines (Itoh et al , ; Croft et al , ; Sadok et al , ) or transgenic models of pancreatic cancer (Rath et al , ). However, our results are in agreement with the recent large‐scale in vivo RNAi screen revealing that loss of Myosin‐II triggers the formation of invasive skin cancers (Schramek et al , ) and that expression of active ROCK2 increases proliferation, but not invasion in similar models (Samuel et al , ).…”
Section: Discussionmentioning
confidence: 88%
“…Fasudil, a potent ROCK inhibitor, also reduced PSC activation in a murine model of PDAC, and led to decreased collagen deposition in the TME, increased gemcitabine delivery, and improved survival [111] (Figure 4). Moreover, inhibition of ROCK-based contractility via the small-molecule inhibitor AT13148 resulted in antitumourigenic effects in both in vitro and in vivo models of PDAC (Figure 4) [112]. The same group also established that activation of ROCK in KPC cancer cells promoted protumourigenic ECM remodelling via matrix metalloproteinase (MMP) secretion [113].…”
Section: Reprogramming Cafs Into Quiescent Fibroblastsmentioning
confidence: 90%
“…Future trials would however need to consider standardisation of the biomarker analysis and interpretation of Merlin loss, sampling of multiple tumour areas where possible to account for potential intratumoural heterogeneity of molecular marker(s) of interest and incorporation of additional promising biomarkers to aid identification of clinical responders to FAK inhibitor-based treatment regimens. Newer ROCK inhibitors (such as ripasudil, CCT129254 or AT13148), are currently being trialled, and utilise a similar 'priming' [92,93] or intermittent regime [201]. Most recently, fasudil, an inexpensive, off-patent ROCK inhibitor, may present a promising new treatment approach for PDAC.…”
Section: Modulation Of the Upstream And Downstream Src Signalling Commentioning
confidence: 99%
“…Src-family kinases (SFKs) not only promote cellmatrix adhesion turnover through FAK, but also regulate Rho family of small GTPases, in particular RhoA and Rac1 activation [85,86]. Rho GTPases are often hijacked by cancers because they regulate diverse cellular processes that are important for tumour growth and metastasis including cytoskeletal dynamics, motility, contractility, cell polarity, membrane transport, gene transcription, as well as regulating the interaction between stromal cells and cancer cells [87][88][89][90][91][92][93]. SFKs control the regulatory molecules of Rho GTPases (guanine nucleotide exchange factors (GEFs), GTPaseactivating proteins (GAPs) and guanine dissociation inhibitors (GDIs)), and it is the tight regulation and extensive crosstalk between Src/FAK and Src/RhoA/ Rac1 that controls integrin-mediated cell adhesion and migration [94][95][96].…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation